2011
DOI: 10.1016/j.brainres.2011.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Rostral ventromedial medulla μ, but not κ, opioid receptors are involved in electroacupuncture anti-hyperalgesia in an inflammatory pain rat model

Abstract: It has been reported that intracerebroventricular injection of a μ receptor antagonist blocked 2 but not 100 Hz electroacupuncture (EA)-produced analgesia in an uninjured animal model. Because persistent pain changes neural response to external stimulation, we hypothesized that the mechanisms of EA anti-hyperalgesia may be different in persistent pain than in health. Hyperalgesia, decreased paw withdrawal latency (PWL) to a noxious thermal stimulus, was induced by subcutaneously injecting complete Freund’s adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…EA stimulation reports showed the analgesic effects of EA in the brain [14, 30, 31]. After EA stimulation, higher levels of brain metabolism were observed in the middle temporal cortex, orbital frontal cortex, insula, middle frontal gyrus, angular gyrus, post-cingulate cortex, precuneus, and middle cingulate cortex [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EA stimulation reports showed the analgesic effects of EA in the brain [14, 30, 31]. After EA stimulation, higher levels of brain metabolism were observed in the middle temporal cortex, orbital frontal cortex, insula, middle frontal gyrus, angular gyrus, post-cingulate cortex, precuneus, and middle cingulate cortex [30].…”
Section: Discussionmentioning
confidence: 99%
“…EA stimulation primarily induces activity in the somatosensory related region, including those in the inferior parietal lobule; secondary somatosensory cortex; insular cortex; and thalamus, except for the superior temporal gyrus [31]. Moreover, EA inhibition of hyperalgesia is involved in the release of mu and delta receptor agonists [32].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated endogenous GABA levels could cause the elevation of beta power [ 41 , 42 ]. Electro acupuncture may induce release of endogenous endomorphins that activate μ opioid receptors in GABA-nergic neurons to suppress the release of GABA [ 43 ]. Taken together, it is conceivable that the decreased power of beta oscillations in our results might reflect the inhibition of GABAergic interneurons by TAES.…”
Section: Discussionmentioning
confidence: 99%
“…Selective μ but not κ receptor antagonists infused into the rostral ventromedial medulla (RVM) blocked 10 and 100 Hz electroacupuncture-produced antihyperalgesia assessed with PWL. 117 Double immunofluorescence staining demonstrated that μ receptor-containing neurons are GABAnergic and that GABAa receptor-containing neurons are serotonergic in the RVM. 117 Hence, electroacupuncture induces release of endogenous endomorphins.…”
Section: Inflammatory Pain Animal Modelsmentioning
confidence: 99%
“…117 Double immunofluorescence staining demonstrated that μ receptor-containing neurons are GABAnergic and that GABAa receptor-containing neurons are serotonergic in the RVM. 117 Hence, electroacupuncture induces release of endogenous endomorphins. These activate μ opioid receptors in GABAnergic neurons that suppress GABA release.…”
Section: Inflammatory Pain Animal Modelsmentioning
confidence: 99%